Najstarsze miejsce kultu św. Agnieszki w świetle "Liber Pontificalis" - Szczur, Piotr (Vox Patrum, 2025)
The purpose of this article is to show the history of the oldest place of veneration of St. Agnes, in light of the accounts contained in the Liber Pontificalis. Firstly, the depiction of St. Agnes from ancient sources, particularly the writings of St. Ambrose and Prudentius, is examined. A thorough analysis and critical assessment of these accounts led to the conclusion that little is known about her life prior to her martyrdom. However, the sources unanimously affirm her status as a virgin and martyr, emphasizing her youth at the time of her death. Beyond this, details about St. Agnes remain uncertain. Subsequently, the accounts of St. Agnes’s veneration in Rome, as recorded in the biographies of four popes, were meticulously analyzed and critically evaluated: Sylvester I (314-335), Liberius (352-366), Innocent I (401-417), and Symmachus (498-514). This analysis and critique of the narratives yielded significant insights. While the information regarding the location of St. Agnes’s worship provided by the compiler of the Liber Pontificalis is largely inaccurate, it does hint at certain themes present in the transmission: the association of St. Agnes with Constantina, a member of the imperial family, who bestowed imperial patronage upon the entire complex of St. Agnes (comprising the basilica and mausoleum) and contributed to the growth of her cult; the profound importance of St. Agnes’s cult to the popes, who, in their efforts to foster its development, sought to exert influence over the shrine of St. Agnes (as seen in the actions of Innocent I) and personally participated in festivities held in her honor (as evidenced by the involvement of Gregory the Great).